M.A.H STORE / Mohd Anikmal Hakim Samsudin - Samsudin, Mohd Anikmal Hakim (2021)
This social media portfolio is one of the assignments for principles of entrepreneurship (ENT530). For this assignment, I need to create a business and do promoting the business by using social media platform. As per requested, I chose to make business that change women appearance for their lifestyle which is knitted cardigan. Knitted cardigan is an apparel that selling various type of design. Our business located at Bandar Parklands Klang, Selangor because it such a great location since it crowded with people around here. It could bring a lot of profits to my business because it easy for them to reach our product and choose what they wants based on the design that have been exposed. My target customer is for those who have an active lifestyle and make a good appearance in public. My store promoting this Knitted Cardigan through Facebook page (FB). This page help boost my business profits and gained a lot of attention from our customers. Knitted carigan is type of wear for those that make the appearance as an important thing for their life. A lot of benefits that my customers can get from M.A.H STORE. We sell various types of knitted cardigan that have many design, sizes, colours that can help people or customer to choose what is they wants. Knitted cardigan is a knitted wear that suitable to use in any condition. A perfect knitted cardigan can give a comfort feeling to the user while they are using it.